Inland Water Fungi in the Anthropocene: Current and Future Perspectives - Grossart, Hans-Peter (2022)
Fungi are increasingly gaining interest from aquatic microbial ecologists. The application of new molecular tools has revealed that they are a ubiquitous and highly diverse organismic group in aquatic environments with essential contributions to aquatic food web dynamics and biogeochemical cycles at the global scale. However, there remain many open questions and knowledge gaps about the consequences of human activities for fungi in aquatic ecosystems. Urban development and anthropogenic pollution provide aquatic fungi with new habitats and substrates but also challenge their adaptive behavior to withstand toxicity and frequent disturbances. In this article, we focus on fungal metabolic capabilities in the light of increasing urbanization. In particular, we investigate the multiple and yet largely unknown effects of microplastics, a steadily increasing anthropogenic pollutant, on aquatic fungal communities. We also make the case that by studying the multiple ecological roles of aquatic fungi, we will better understand the impacts of urban development and anthropogenic pollution on human and environmental health.